High-resolution mapping of cell cycle dynamics during steady-state T cell development and regeneration in vivo - Kunze-Schumacher, Heike; Verheyden, Nikita A.; Grewers, Zoe; Meyer-Hermann, Michael; Greiff, Victor; Robert, Philippe A.; Krueger, Andreas; Justus Liebig University Giessen (My University, 2025)
Control of cell proliferation is critical for the lymphocyte life cycle. However, little is known about how stage- specific alterations in cell cycle behavior drive proliferation dynamics during T cell development. Here, we employed in vivo dual-nucleoside pulse labeling combined with the determination of DNA replication over time as well as fluorescent ubiquitination-based cell cycle indicator mice to establish a quantitative high-resolution map of cell cycle kinetics of thymocytes. We developed an agent-based mathematical model of T cell developmental dynamics. To generate the capacity for proliferative bursts, cell cycle acceleration followed a ‘‘stretch model’’ characterized by the simultaneous and proportional contraction of both G1 and S phases. Analysis of cell cycle phase dynamics during regeneration showed tailored adjustments of cell cycle Phase dynamics. Taken together, our results highlight intrathymic cell cycle regulation as an adjustable system to maintain physiologic tissue homeostasis and foster our understanding of dysregulation of the T cell developmental program.
Keywords: ddc:570